Semeando a cidade: provisão de serviços ecossistêmicos na agricultura urbana - Corrêa, Carina Júlia Pensa (Universidade Federal de São Carlos, 2020)
Urban density triggers several environmental and social problems, most of them associated with the difficulty of maintaining and providing ecosystem services in these landscapes. In this sense, interventions are necessary to guarantee the quality of life of the population combined with environmental conservation. Although urban agriculture is driven by its provision (food production) and cultural (leisure and social well-being) services, they produce essential support and regulatory functions, such as reducing heat islands, attracting pollinators, biodiversity, and carbon sequestration. The present study evaluated the socio-environmental characteristics of urban gardens and their role in providing these ecosystem services, especially for water regulation. In a comparative study, gardens in São Paulo, Paris, and England were analyzed according to social, environmental, and political indicators. The motivations of gardeners include food security, quality of life, environmental education, integration, and social inclusion. Agroecological practices were positive results found in the visited experiences, which allow the generation of ecosystem services in all categories. From a social point of view, a continuous program of support to farmers could bring more security to the practice in São Paulo. Regarding the behavior of the soil in these spaces, annual monitoring of soil density, humidity, hydraulic conductivity, water infiltration speed, and mechanical resistance to penetration was carried out in vegetable gardens, vacant lots, squares, and riparian forests. The gardens obtained the best results in all the adopted indicators, and thus, they respond better to a rain event when compared to vacant lots, squares, and riparian zones studied. Besides, urban riparian forests may have difficulty in infiltrating water and high soil compaction, and actions to improve their ecological function are important. Similar results were found in the case study carried out in the Corujas watershed, in São Paulo. The soil of the Corujas garden, installed on the same perimeter as the square and a partially concrete permanent preservation area, has lower compaction rates, and, therefore, more significant potential to contribute to rainfall infiltration. The example of this garden also shows that it is possible to combine planting with the installation of green infrastructures, such as rain gardens. The development and maintenance of spaces that generate multiple ecosystem services in cities should be encouraged, and it is concluded that urban agriculture, in addition to invaluable social benefits, has great potential for improving water regulation in cities.
Seeding the city: ecosystem services provision in urban agriculture
Keywords: Hortas urbanas; Serviços ecossistêmicos; Regulação hídrica; Indicadores do solo; Manejo de bacias hidrográficas; Urban gardens; Ecosystem Services; Water regulation; Soil indicators; Watershed management; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS